2017
DOI: 10.1002/etc.3892
|View full text |Cite
|
Sign up to set email alerts
|

Using ultrahigh‐resolution mass spectrometry and toxicity identification techniques to characterize the toxicity of oil sands process‐affected water: The case for classical naphthenic acids

Abstract: Previous assessments of oil sands process-affected water (OSPW) toxicity were hampered by lack of high-resolution analytical analysis, use of nonstandard toxicity methods, and variability between OSPW samples. We integrated ultrahigh-resolution mass spectrometry with a toxicity identification evaluation (TIE) approach to quantitatively identify the primary cause of acute toxicity of OSPW to rainbow trout (Oncorhynchus mykiss). The initial characterization of OSPW toxicity indicated that toxicity was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…It is therefore essential that this is taken into account when comparing data between laboratories. In addition, recent toxicity techniques (Hughes et al, 2017;Morandi et al, 2015) rely heavily upon mass spectrometric data, both quantitatively and qualitatively, for the identification of principal toxic components that attribute to end-point responses being measured. Depending upon the apparent pH (basic/acidic) of the eluent being used, the interpretation of the mass spectrometric data would have a significant impact upon the assignment of which components are contributing towards the toxicity of the sample.…”
Section: Ft-icr Msmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore essential that this is taken into account when comparing data between laboratories. In addition, recent toxicity techniques (Hughes et al, 2017;Morandi et al, 2015) rely heavily upon mass spectrometric data, both quantitatively and qualitatively, for the identification of principal toxic components that attribute to end-point responses being measured. Depending upon the apparent pH (basic/acidic) of the eluent being used, the interpretation of the mass spectrometric data would have a significant impact upon the assignment of which components are contributing towards the toxicity of the sample.…”
Section: Ft-icr Msmentioning
confidence: 99%
“…Sample introductions by flow injection without chromatography and with full chromatographic separations are currently used, both with success (Headley et al, 2016;Headley et al, 2013 and trends observed are independent of the instrument used. Furthermore, transfer solvent apparent pH has a critical impact upon data sets that were acquired using different analytical protocols and used for comparative environmental and monitoring studies along with toxicological investigations (Hughes et al, 2017;Morandi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical constituents in OSPW are likely attributed to the physical structure and chemical composition of the oil sand ore being extracted. In recent years, improvements in advanced chromatographic separation and high‐resolution mass spectrometric techniques have greatly expanded the understanding of the chemical complexity of OSPW and other bitumen‐influenced waters (Rowland, Scarlett et al ; Rowland, West et al ; Jones et al ; Headley, Peru, Mohamed et al ; Noestheden et al 2014; Ortiz et al 2014; Pereira and Martin ; Brunswick et al , , ; Hughes, Mahaffey et al ; Kovalchik et al ). This improved ability to characterize OSPW and its constituents has enabled improved targeted toxicological studies on specific fractions of OSPW (Hughes, Huang et al ; Morandi et al ; Bauer ).…”
Section: Workhop Frameworkmentioning
confidence: 99%
“…As noted in the Oil sands process water chemistry section, the composition is broader than the classic naphthenic acids and includes a variety of charged and polar structures, and some molecules with integrated N and S. Work continues to identify the toxic fractions of bioavailable mixtures of chemicals in OSPW using effects‐directed analyses (Yue et al 2014; Zhang et al ; Morandi et al ; Hughes, Mahaffey et al ; McQueen, Kinley et al ; Bauer ) coupled with conventional and high‐resolution analytical techniques, as well as novel passive sampling methods to measure the bioavailable organics in OSPW (Redman et al ).…”
Section: Workhop Frameworkmentioning
confidence: 99%
“…The toxicity of the OSPW has mainly been attributed to the presence of naphthenic acids (NAs) (MacKinnon and Boerger, 1986). The O 2 family is represented by classical NAs with just one carboxylic acid group or dihydroxy groups, and published data concur that O 2 species are the main toxic and classical NAs in OSPW (Morandi et al, 2015;Hughes et al, 2017;Huang et al, 2018). The term NAs refers to all the carboxylic acids present in crude oil and these are now classified as emerging water contaminants (Richardson and Ternes, 2018).…”
Section: Introductionmentioning
confidence: 99%